Goldmine tailings : a remote sensing survey - Khumalo, Bheki, Romeo (My University, 2004)
Pollution originating from mine tailings is currently one of the environmental problems South Africa has to deal with. Because of the large number of tailings impoundments and their changing status, authorities are battling to keep their records and controls up to date. This project is aimed at investigating the use of remote sensing as a way of conducting surveys of mine tailings efficiently, regularly and at a low cost. Mine tailings impoundments of the Witwatersrand in Gauteng provide an ideal study area because of the large number of tailings dams of different sizes and conditions and the availability of satellite images and aerial photographs covering the area. Tailings impoundments conditions are analysed through satellite images, airborne multi-spectral data and aerial photographs captured during the Safari 2000 dry season campaign. Remote sensing interpretation of colour composites of multi-spectral bands, Principal Components and supervised and unsupervised classifications are the methods of analysis used. The overall goal of the project has been achieved through the production of a comprehensive database of tailings impoundments and their rehabilitation status, in an accessible format, containing identity, coordinates, area, rehabilitation status and owner of each tailings impoundment, map them and end up with a comprehensive database of tailings impoundment on the Witwatersrand.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Environmental Science
Keywords: Environmental sciences -- remote sensing; Remote sensing; Aerial photography; Gold mines and mining -- South Africa; Tailing dams